Resistance and adaptation: The colonial government and native elites - Spalding, Karen (1981)
Colonial control depends largely on the cooperation of the conquered; Without the consent of the conquered society to their own rule, the conquerors would lack access to the social and political mechanisms that made their cohesion possible and regulated the behavior of their members. Colonial control required that some members of the conquered society participate to some degree in the benefits extracted, their loyalty being compensated by the prestige and power derived from the support provided by the new rulers.